Efeito de substratos e da adubação no crescimento e na qualidade de mudas de Inga laurina (Sw.) Willd. (Fabaceae) - Jesus, Murilo Figueredo Campos de (2013)
The production of high quality seedlings is important for the success of forest restoration programs. The aim of this study was to evaluate the effect of mixtures of a commercial substrate and coir dust for the production of Inga laurina seedlings. Two experiments were mounted in a generalized randomized block design, with four blocks, three replicates within the blocks and three seedlings per replication. Polyethylene tubes were filled with four mixtures (v:v) of a commercial substrate HS Florestal (HSF) and coir dust (CD) in the following proportions: T1 = 100% HSF, T2 = 80% HSF + 20% CD, T3 = 60% HSF + 40% CD and T4 = 40% HSF + 60% CD. The experiments were conducted independently, with (experiment I) and without (experiment II) supplemental fertilization. Measurements of seedlings growth and quality were made at the time of transplanting and at the end of the experiments, 81 days (experiment I) and 110 days (experiment II). The results were submitted to the analysis of variance followed by Tukey test at 5% probability for statistical comparison. Using supplemental fertilization there was no difference in the growth and quality of the seedlings up to 60% coir dust added to the commercial substrate. In the absence of supplemental fertilization, a mix of 80% HSF + 20% PC is indicated for the production of I. laurina seedlings.